1998
DOI: 10.1021/je980184l
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Fish Oil Components in Supercritical CO2 and CO2 + Ethanol Mixtures

Abstract: Solubility measurements for squalene, vitamin A palmitate, orange roughy oil, spiny dogfish liver oil, and commercial cod liver oil in supercritical carbon dioxide are reported over the temperature range 313−333 K and pressure range 200−300 bar. Solubility measurements are also reported for squalene, orange roughy oil, spiny dogfish liver oil, and cod liver oil in supercritical carbon dioxide + ethanol mixtures over the pressure range 200−300 bar at 333 K, and ethanol mass concentrations up to 12% by mass on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 15 publications
(18 reference statements)
4
39
0
Order By: Relevance
“…They observed that, at constant temperature, fish oil solubility increased significantly with pressure, whereas, at constant pressure, oil solubility decreased with temperature up to a pressure value from which oil solubility began to increase as temperature increased. This crossover behaviour has also been observed in other natural fish oils from sand eel (Borch-Jensen & Mollerup, 1997), orange roughy, spiny dogfish liver or cod liver (Catchpole, Grey, & Noermark, 1998). It is explained considering that, at constant pressure, a temperature increase has a double effect: the density of the solvent decreases, which would make solubility to decrease, and the vapour pressure of the solute increases, which would make the solubility to increase.…”
Section: Supercritical Fluid Extraction (Sfe)supporting
confidence: 58%
See 1 more Smart Citation
“…They observed that, at constant temperature, fish oil solubility increased significantly with pressure, whereas, at constant pressure, oil solubility decreased with temperature up to a pressure value from which oil solubility began to increase as temperature increased. This crossover behaviour has also been observed in other natural fish oils from sand eel (Borch-Jensen & Mollerup, 1997), orange roughy, spiny dogfish liver or cod liver (Catchpole, Grey, & Noermark, 1998). It is explained considering that, at constant pressure, a temperature increase has a double effect: the density of the solvent decreases, which would make solubility to decrease, and the vapour pressure of the solute increases, which would make the solubility to increase.…”
Section: Supercritical Fluid Extraction (Sfe)supporting
confidence: 58%
“…At low pressures the first effect predominates and at high pressures is the solute vapour pressure effect which becomes stronger (Brunner, 1994). It has been also observed that fish oil solubility increases by adding polar co-solvents such as ethanol (Catchpole et al, 1998).…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Squalene equilibrium constant (k sq = weight fraction in vapor phase/weight fraction in liquid phase) in squalene + CO 2 binary mixtures. Comparison between experimental data [30,31] at (᭹) 313 K and ( ) 333 K and GC-EoS calculations using (· · ·) original parameters (Tables 1-3) and (-) parameters for high molecular weight compounds (Table 4). …”
Section: Application To the Vle Modeling Of Co 2 And Main Constituentmentioning
confidence: 99%
“…Ethanol is commonly used as cosolvent or modifier for the extraction of natural products because the toxicity of ethanol to the human body is low (Catchpole, Grey, & Noermark, 1998;Temelli, 1992;Walsh, Greenfield, Ikonomou, & Donohue, 1989;Walsh & Ikonomou, 1987). Furthermore, it can be easily removed from the food matrix although there is a limited information regarding the effect of ethanol and other cosolvents on the SC-CO 2 extraction of cocoa butter.…”
Section: Introductionmentioning
confidence: 99%